Analisa Perancangan Sistem Barcode Pada Departemen Kain Di PT Samwon Busana Indonesia Semarang - Anggaeni, Mei; Sukur, Muji (MEANS (Media Informasi Analisa dan Sistem), 2024)
For warehouse management, PT Samwon Busana Indonesia Semarang still uses a manual system until now. For example, operators use computers to summarize the data entered after writing down the fabric requirements on paper and sticking them on the fabric. Likewise, all recording tasks are completed manually when storing and issuing fabrics. This manual recording also has constraints, namely increasing the delay time from when the fabric arrives until it is sent to the production section. Operators often need time to enter data and find a place to store the fabric that will be given to the production section, which causes the process to be delayed and has an impact on several things, such as time and cost. The purpose of this project is to create a barcode-based inventory system that will help the Fabric Department of PT Samwon Busana Indonesia Semarang in recording products, outgoing goods, incoming goods, and stock of goods using the FIFO approach. Inventory of goods at PT Samwon Busana Indonesia Semarang can be managed through the use of a barcode system in the Fabric Department. This system consists of a transaction process for incoming goods that has the potential to increase stock of goods and transactions for outgoing goods that have the potential to reduce stock of goods automatically using the FIFO approach